PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DISIPLIN KERJA DAN TINGKAT PENDIDIKAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA PRAYA - ULFIYANI ASDIANSYURI (Universitas Mahasaraswati K. Mataram, 2021)
The development of a company is not separated from the performance of human resources in it such as motivation, leadership style, work discipline and level of education greatly affect a person in producing maximum results in order to achieve company goals. This study aims to determine the partial and simultaneous influence of the variables of leadership style, motivation, work discipline and education level on employee work productivity at the Pratama Praya Tax Office. This type of research is associative by using a sample of 50 employees of the Pratama Praya tax office. The results of this study indicate that the variables of motivation, work discipline and level of education partially affect the work productivity of employees at the Pratama Praya Tax Office while Leadership Style does not partially affect the work productivity of employees at the Pratama Praya Tax Office and the variables of leadership style, motivation, work discipline and education level have a simultaneous effect on employee work productivity at the Pratama Praya Tax Service Office with F count greater than F table of 14,732 > from f table 2.86.